Design approach for flexural capacity of concrete T-beams with bonded prestressed and nonprestressed FRP reinforcements. (15th November 2018) - Peng, Fei; Xue, Weichen
Abstract: Concrete beams with prestressed and nonprestressed fiber-reinforced polymer (FRP) reinforcements are commonly employed in field applications. However, available flexural strength design approaches mainly focus on rectangular concrete beams exclusively prestressed with FRP tendons. This paper, therefore, presents a simplified yet rational design approach for flexural capacity of concrete T-beams with bonded prestressed and nonprestressed FRP reinforcements. Firstly, a new transition region between tension- and compression- controlled sections was proposed in terms of ratio of provided-to-balanced reinforcement ( ρe, b < ρe ≤ 1.5 ρe, b ) based on a statistical analysis of an experimental database of 83 beams. Afterwards, numerical sectional analysis procedure of tension-controlled sections was developed by using an accurate stress block to approximate the nonlinear compressive stress distribution in concrete. Based on a detailed parametric study of over 160, 000 sections, simplifed design equations for flexural capacity of tension-controlled section is derived from multiple regression analyses. Then, design equations were presented for flexural capacity of compression-controlled sections. Finally, the performance of the proposed approach was evaluated by comparing their predictions with experimental results of the 83 beams.